3D Fe3O4@Au@Ag nanoflowers assembled magnetoplasmonic chains for in situ SERS monitoring of plasmon-assisted catalytic reactions. Issue 22 (20th May 2016) - Ding, Qianqian; Zhou, Hongjian; Zhang, Haimin; Zhang, Yunxia; Wang, Guozhong; Zhao, Huijun
Abstract : A 3D Fe3 O4 @Au@Ag nanoflower assembled magnetoplasmonic chains used for in situ SERS monitoring of catalytic reactions and was constructed with 3D nanoflower shaped silver nanoplates coated on the magnetoplasmonic nanochains via a magnetic field induced assembly. Abstract : One-dimensional (1D) assembled magnetoplasmonic nanochains (MPNCs) were fabricated using Fe3 O4 @Au core–shell nanoparticles (NPs) via a magnetic field induced assembly. With the help of a silver growth solution, the 3D Fe3 O4 @Au@Ag nanoflowers assembled magnetoplasmonic chains (Fe3 O4 @Au@Ag NAMPCs) were prepared via an in situ reduction method. A heterogeneous epitaxial growth mechanism was proposed to explain the growth process of the Fe3 O4 @Au@Ag NAMPCs. The Fe3 O4 @Au@Ag NAMPCs possessed large numbers of hot spots within the highly ordered structure and were used as a SERS substrate to enhance the sensitivity, uniformity and reproducibility of Raman signals. Subsequently, the Fe3 O4 @Au@Ag NAMPCs, integrating a heterogeneous catalysis and in situ SERS detection, was assessed to monitor the catalytic reduction of 4-nitrothiophenol (4-NTP) to p, p ′-dimercaptoazobenzene (DMAB).